3D art essentials : the fundamentals of 3D modeling, texturing, and animation - Chopine, Ami. (Amsterdam ; Boston : Elsevier/Focal Press, 2011)
Looks at the principles of 3D art and offers instructions on creating a variety of 3D graphics and animation.
A history of computer graphics and special effects -- Getting started and getting finished -- Polygons : how 2D becomes 3D -- NURBS : the spliny truth -- Subdivision surfaces : the marriage of polygons and NURBS -- Deforming : it's a good thing -- Rigging -- Animation : it's alive! -- Dynamics : let's get physical -- How the pixel gets its color -- More than just color -- Light effects -- Lighting the way -- Working the camera -- Environments -- Rendering -- Procedures and graphs -- Scripting -- What tools to use -- Making a career out of 3D.
"Geek At Play Studio"--Cover.
Includes bibliographical references (p. 261-262) and index.
Keywords: Computer graphics; Computer animation; Three-dimensional display systems; Computer graphics; Computer animation; Computeranimation. -- (DE-588c)4199710-4; Dreidimensionale Computergraphik. -- (DE-588c)4133691-4